Enhancing Digital Security via E-Law Optimization and Deepfake Regulation: A Comparative Study of China - Widya Tri Lestari; Reva Fitri Ramadani; Yasinta Diva Negara; Fadli Ananda Putra (Journal of Ius Comparatum Law Studies, 2025)
The development of artificial intelligence (AI), especially deepfake technology, presents new challenges in the realm of law and digital security. Although initially developed for the purposes of the creative industry, this technology is often misused to spread false information, defamation, and even extortion. Indonesia does not yet have regulations that specifically regulate deepfake, so law enforcement against its misuse still relies on the Electronic Information and Transactions Law (UU ITE), which does not explicitly cover this technology. This study discusses the urgency of deepfake regulation in Indonesia by analyzing the "Deep Synthesis Provisions" policy implemented in China. The results of the analysis show that an adaptive regulatory approach, co-regulation, development of detection technology, increasing digital literacy, and a multistakeholder framework can be solutions in formulating deepfake regulations in Indonesia. Therefore, a revision of the ITE Law is needed to include specific regulations regarding deepfake, as well as collaboration between the government, technology industry, and society to ensure the responsible and ethical use of AI.